Oligophrenin-1 (Ophn1) is expressed in mouse retinal vessels - Sel, Saadettin; Kaiser, Maja; Nass, Norbert; Trau, Stefanie; Roepke, Albrecht; Storsberg, Joachim; Hampel, Ulrike; Paulsen, Friedrich; Kalinski, Thomas (Gene Expression Patterns, 2012)
The Rho GTPase activating protein (RhoGAP) Oligophrenin 1 (Ophn1) regulates numerous members of the Rho family that are involved in neuronal morphogenesis of the central and peripheral nervous system. In the present study we investigated the spatial and temporal expression of Ophn1 in the mouse eye. The expression of Ophn1 was analysed on both mRNA and protein level. To identify the Ophn1 transcripts, adult retina and cerebrum (positive control) of postnatal day (P) 158 was subjected to reverse transcription polymerase chain reaction (RT-PCR) and sequencing of the amplified cDNA. The Ophn1 protein was analyzed in adult retina by Western blotting and in developing eyes at embryonic day (E) 12, E14, E16, E18, P0, P3, P7, P14 and P158 by immunohistochemistry. Ophn1 transcripts were detected in adult retina by RT-PCR and confirmed by sequencing. Western blot analysis revealed the expression of Ophn1 protein in the adult retina. Immunohistochemical examination of developing eyes localized the protein to retinal vasculature with an onset of Ophn1 expression from P14 onwards. The specific expression pattern suggests that Ophn1 could have a physiological role in the retinal vasculatures. At P14, the vessel development in the retina is widely completed, implying that Ophn1 has either a function during adulthood or for the generation of the intermediate plexus during the late vessel development of the retina.
EVALuna2:4385